Synthesis and Electroluminescent Properties of Through-Space Charge Transfer Polymers Containing Acridan Donor and Triarylboron Acceptors - Chen, Fan; Hu, Jun; Wang, Xingdong; Shao, Shiyang; Wang, Lixiang; Jing, Xiabin; Wang, Fosong (Frontiers in Chemistry, 2019)
We report the design, synthesis and electroluminescent properties of three kinds of through-space charge transfer (TSCT) polymers consisting of non-conjugated polystyrene backbone, acridan donor and triarylboron acceptors having different substituents such as hydrogen (H), fluorine (F), and trifluoromethyl (CF3). Owing to the weak electron interaction between acridan donor and triarylboron acceptor through non-conjugated connection, blue emission with peaks in range of 429 nm to 483 nm can be achieved for the polymers in solid-state film, accompanied with photoluminescence quantum yields of 26–53%. The resulting TSCT polymers exhibit small ∆EST values below 0.1 eV owing to the separated HOMO and LUMO distributions, showing thermally activated delayed fluorescence with lifetimes in range of 0.19–0.98 μs. Meanwhile, the polymers show aggregation-induced emission (AIE) effect with the emission intensity increased by up to ~33 folds from solution to aggregation state. Solution-processed organic light-emitting diodes based on the polymers containing trifluoromethyl substituent exhibit promising electroluminescent performance with maximum luminous efficiency of 20.1 cd A-1 and maximum external quantum efficiency of 7.0%, indicating that they are good candidates for development of luminescent polymers.